Correction: Zhou et al. Optimization of Blasting Parameters Considering Both Vibration Reduction and Profile Control: A Case Study in a Mountain Hard Rock Tunnel. Buildings 2024, 14, 1421 - Zhou, Junjie; Gao, Shan; Luo, Pingkuang; Fan, Jiale; Zhao, Congcong (Buildings (Basel), 2024)
Missing Citation [...]